Hubungan Ketepatan Penggunaan Baby Walker dengan Perkembangan Motorik Kasar Anak Usia 12-18 Bulan di Wilayah Kerja Puskesmas Langsa Kota - Hanum, Parida; Kamaliah, Kamaliah; Purba, Junita; Karlina, Karlina; Nasution, Karlina Sari; Sitorus, Karolina (Universitas Malahayati, 2024)
ABSTRACT Children's motor development is a mandatory thing that children must have and fulfill. In 2020, around 35.4% of children in Indonesia suffered from deviations in gross motor skills, fine motor skills, as well as mental and emotional disorders. The correct use of a baby walker is believed to be effective in helping children walk faster so that their gross motor development in terms of the process of learning to walk will be better. This study aims to determine the relationship between the accuracy of using a baby walker and the gross motor development of children aged 12-18 months in the Langsa City Health Center UPTD Work Area. This research is a quantitative research with a descriptive correlation type using a cross sectional design. The sampling technique in this research used a purposive sampling technique of 52 respondents. Researchers collected data directly from interviews with mothers and assessments of gross motor development (KPSP) of children aged 12-18 months. Data analysis was carried out univariate and bivariate using the chi square test. The results of the study showed that the majority of children aged 12-18 months were given inappropriate use of baby walkers, namely 32 respondents (61.5%). Most of the gross motor development of children aged 12-18 months was in the doubtful category, as many as 31 children (59.6%) and a small number had gross motor development in the deviation category, as many as 3 children (5.8%). There is a relationship between the accuracy of using a baby walker and the gross motor development of children aged 12-18 months with a p-value of 0.001 (p<0.05). The conclusion of this research is that there is a relationship between the accuracy of using a baby walker and the gross motor development of children aged 12-18 months in the UPTD Working Area of the Langsa City Health Center. It is hoped that breastfeeding mothers can obtain information regarding the proper use of baby walkers so that they can help the development of gross motor skills in children aged 12-18 months. Keywords: Baby Walker, Gross Motor, Children Aged 12-18 Months ABSTRAK Perkembangan motorik anak menjadi satu hal wajib yang harus dimiliki dan dipenuhi oleh anak. Pada tahun 2020 sekitar 35,4% anak di Indonesia menderita penyimpangan dalam motorik kasar, motorik halus, serta penyimpangan mental emosional. Penggunaan baby walker yang tepat dipercaya efektif untuk membantu anak berjalan lebih cepat sehingga perkembangan motorik kasarnya dalam hal proses belajar berjalan akan lebih baik. Penelitian ini bertujuan untuk mengetahui hubungan ketepatan penggunaan baby walker dengan perkembangan motorik kasar anak usia 12-18 bulan di Wilayah Kerja UPTD Puskesmas Langsa Kota. Penelitian ini adalah penelitian kuantitatif dengan jenis deskriptif korelasi menggunakan rancangan cross sectional. Teknik pengambilan sampel dalam penelitian ini menggunakan teknik purposive sampling sebanyak 52 responden. Peneliti mengumpulkan data langsung dari hasil wawancara kepada ibu dan pengkajian perkembangan motorik kasar (KPSP) anak usia 12-18 bulan. Analisa data dilakukan secara univariat dan bivariat menggunakan uji chi square. Hasil penelitian menunjukkan bahwa sebagian besar anak usia 12-18 bulan diberikan penggunaan baby walker secara kurang tepat sebanyak 32 responden (61,5%). Perkembangan motorik kasar anak usia 12-18 bulan sebagian besar dalam kategori yang meragukan sebanyak 31 anak (59,6%) dan sebagian kecil memiliki perkembangan motorik kasar dalam kategori penyimpangan sebanyak 3 anak (5,8%). Ada hubungan ketepatan penggunaan baby walker dengan perkembangan motorik kasar anak usia 12-18 bulan dengan p-value 0,001 (p<0,05). Kesimpulan penelitian ini adalah ada hubungan ketepatan penggunaan baby walker dengan perkembangan motorik kasar anak usia 12-18 bulan di Wilayah Kerja UPTD Puskesmas Langsa Kota. Diharapkan bagi ibu menyusui untuk dapat memperoleh informasi mengenai penggunaan baby walker secara tepat agar dapat membantu perkembangan motorik kasar pada anak usia 12-18 bulan. Kata Kunci: Baby Walker, Motorik Kasar, Anak Usia 12-18 Bulan